Optimización de recorridos y frecuencias en un sistema BRT (2020)
Currently, the transport of passengers within large cities has become a priority problem for their development and operation, for this reason, different approaches have been implemented to solve this problem known as TNDP (Transit Network Design Problem). The city of Bogotá has the Transmilenio BRT system, which is considered one of the great feats of mobility in Latin America, however, the level of user satisfaction with the system does not exceed 20%, mainly due to overcrowding of users in the trunk system, the number of users has exceeded the capacity of both stations and buses during peak hours. For this reason, this undergraduate project seeks to take advantage of the incorporation of the new bus fleet, which has bi- articulated vehicles, and to propose, through the implementation of a multi-objective optimization method, a new set of routes and frequencies that focus on regulating occupancy average within the buses. On the other hand, a proposal is presented for the size of the stations according to the new distribution of the routes in order to improve the experience of the users of the trunk service by reducing both the average occupancy of the buses and the waiting times inside the stations without losing sight of the needs of the service provider, trying to minimize the necessary number of buses.